Distinguishing Ewing sarcoma and osteomyelitis using FTIR spectroscopy. Issue 1 (December 2018) - Chaber, Radosław; Arthur, Christopher; Depciuch, Joanna; Łach, Kornelia; Raciborska, Anna; Michalak, Elżbieta; Cebulski, Józef
Abstract The differential diagnosis of Ewing sarcoma and osteomyelitis can be challenging and can lead to delays in treatment with possibly devastating results. In this retrospective, small-cohort study we demonstrate, that the Fourier Transformed Infrared (FTIR) spectra of osteomyelitis bone tissue can be differentiated from Ewing sarcoma and normal bone tissue sampled outside tumour area. Significant differences in osteomyelitis samples can be seen in lipid and protein composition. Supervised learning using a quadratic discriminant analysis classifier was able to differentiate the osteomyelitis samples with high accuracy. FTIR spectroscopy, alongside routine radiological and histopathological methods, may offer an additional tool for the differential diagnosis of osteomyelitis and ES.